Revisiting Banking Stability Using a New Panel Cointegration Test - Hassan B. Ghassan; Zakaria Boulanouar; Kabir M. Hassan (International Journal of Financial Studies, 2021)
Using a new panel cointegration test that considers serial correlation and cross-section dependence on a mixed and heterogenous sample of Saudi banks, we revisit the cointegrating equation of the z-score index of banking stability. Our results show that even when we consider the cross-section dependency and serial correlation of the errors, there is a possibility of a long-run relationship, which holds in our sample of banks. Furthermore, in the medium term, we found some banks to be integrated, whereas others were non-cointegrated. We interpret this to suggest that some banks contribute to banking stability, whereas others do not. In other words, there exists at least one bank that acts as a destabilizer and the challenge for financial regulators is to identify which banks these are. However, the current version of the Hadri et al. test does not allow for the identification of the non-cointegrated banks. If the test was able to do that, the regulatory authorities would be able to develop corrective policies/measures specifically tailored to the non-cointegrated units.